Production of Nutritious and Healthy Functional Vegetarian Bars for Fitness Athletes - Ghada, M. Youssef; Heba, A. Barakat; Mai, M.M. Naeem (Food Technology Research Journal, 2024)
With the development of the food trade, tremendous changes in the eating patterns of athletes have been observed. Bars represent convenient, ready-to-eat and properly portioned food items that not only provide the body with nutrients but also provide a feeling of satiety. This study aimed to formulate new high-protein and energy plant-based functional bars for athletes. Eight bars were formulated from plant sources and spirulina with different salty and sweet flavors. The bars were evaluated for chemical composition and content of minerals, phenolic and flavonoids. Protein digestibility in vitro and antioxidant activity were estimated, and sensory properties were evaluated, as well as caloric values ​​and recommended dietary allowances (RDA). The results confirmed that the protein content of the bars ranged from 13.3 to 25.79%, energy from 456.28 to 528.64 kcal/100 g, potassium and iron from 3373.82 to 4901.91 ppm and 106.95 to 603.77 ppm, respectively. The protein digestibility values ​​ranged from 45.86 to 76.45%. The sensory evaluation results showed that all bar formulas were acceptable with values ​​ranging from 6.5 to 9 for general acceptability. The shelf life of the bars was 7 weeks at room temperature (25-30°C), while it reached 11 weeks at 4°C. In conclusion, manufactured bar formulas with high acceptability and antioxidant activity can provide athletes and consumers in general with a high percentage of their nutrient requirements.